Up-regulation of CB1 cannabinoid receptors located at glutamatergic terminals in the medial prefrontal cortex of the obese Zucker rat - Leyre Echeazarra; Leyre Echeazarra; Sergio Barrondo; Sergio Barrondo; Sergio Barrondo; Gontzal García del Caño; Gontzal García del Caño; Itziar Bonilla-Del Río; Itziar Bonilla-Del Río; Jon Egaña-Huguet; Jon Egaña-Huguet; Nagore Puente; et al. (Frontiers Media S.A., 2022)
The present study describes a detailed neuroanatomical distribution map of the cannabinoid type 1 (CB1) receptor, along with the biochemical characterization of the expression and functional coupling to their cognate Gi/o proteins in the medial prefrontal cortex (mPCx) of the obese Zucker rats. The CB1 receptor density was higher in the prelimbic (PL) and infralimbic (IL) subregions of the mPCx of obese Zucker rats relative to their lean littermates which was associated with a higher percentage of CB1 receptor immunopositive excitatory presynaptic terminals in PL and IL. Also, a higher expression of CB1 receptors and WIN55,212-2-stimulated [35S]GTPγS binding was observed in the mPCx but not in the neocortex (NCx) and hippocampus of obese rats. Low-frequency stimulation in layers II/III of the mPCx induced CB1 receptor-dependent long-term synaptic plasticity in IL of area obese Zucker but not lean rats. Overall, the elevated 2-AG levels, up-regulation of CB1 receptors, and increased agonist-stimulated [35S]GTPγS binding strongly suggest that hyperactivity of the endocannabinoid signaling takes place at the glutamatergic terminals of the mPCx in the obese Zucker rat. These findings could endorse the importance of the CB1 receptors located in the mPCx in the development of obesity in Zucker rats.